Habitat-specific temporal variation in the pace of fish diversification - Nick Peoples; Michalis Mihalitsis; Peter C. Wainwright (Proceedings of the National Academy of Sciences, 2026)
Speciation and extinction events are concentrated unevenly through space and time, shaping the global distribution of extant biodiversity. Habitats modulate these dynamics over short timescales by determining the ecological landscape and providing substrate for diversification. This raises questions about whether biotic and abiotic heterogeneity across habitats also influenced diversification rate over geological timescales. Here, we show the rate of species diversification varies through time according to major differences between aquatic habitats for ray-finned fishes, which comprise over half of vertebrate diversity. Phylogeny-wide net diversification rates have accelerated 1.5 to 1.7× in reef-associated, freshwater benthopelagic, and freshwater demersal lineages, which inhabit complex benthic habitats, while remaining constant through time in other less complex habitats such as the pelagic zone. Combined evidence across multiple diversification models implicates the rise of benthic-feeding fishes, which capitalized on functional feeding innovations and the reorganization of benthic resources following the Paleocene–Eocene Thermal Maximum. Our results show that the global biodiversity of ray-finned fishes is shaped by a combination of clade-specific pulses and tree-wide rate shifts, an outcome of the dynamic interplay between the traits of species and the features of the habitats they occupy.